The Movement of Economy Islamization Based on Local Wisdom in Pamekasan - Zainal Abidin (Institut Agama Islam Negeri Madura, 2017)
The Assessment and implementation of Islamic Shari'a agency (LP2SI) has a significant role in the development of Pamekasan, one of which in the economic sector development. However, as a drafter and not as a practitioner, LP2SI has some limited authority. Furthermore, it seems that the human resources of LP2SI have also some constrains so far. The role of LP2SI stems from a mindset that has been structured so as to produce some concepts including in the economic areas. The relation between the mindset and Islamic economics then gives rise to Islamic economics schools. In the spectrum of economic thought, LP2SI, can be classified into the thought of mainstream.